Solar Energy Application in Malaysia’s Manufacturing Industry: Analysis of the Challenges and Success Factors - Sharni Ahamad Sabki; Hawa Hishamuddin; Muhammad Idham Sabtu; Zaliha Wahid (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study analyzes challenges and success factors in the use of solar energy in Malaysia’s manufacturing sector. A hierarchical tree based on the Analytical Hierarchy Process (AHP) method was modeled to identify the sub-criteria of challenge aspects and success factors. A questionnaire study based on the sub-criteria was conducted on 30 respondents among supervisors and above from various companies involved in the electrical, electronic, and mechanical manufacturing industries that employ machines intensively in the Klang Valley area, Malaysia. Data for the study were collected from survey respondents’ evaluations. The collected data was analyzed using the AHP method. Findings show that there is a signifi cant positive relationship between the challenges and success factors of implementing solar energy in the manufacturing industry in Malaysia. As a result of the study, government initiatives are the key challenges and success factors for the industry involved in utilizing solar energy. The development of a framework for solving the challenge of using solar energy in the industry has been proposed. As a result, the framework can provide added value to government and funding agencies involved in improving Malaysia’s solar energy policy. This contribution will assist them with drafting, developing, and improving existing policies and plans, thereby, leading to more solar energy usage in Malaysia’s manufacturing industry.